A simple method for preparing super-hydrophobic powder from paper sludge ash - Spathi,C; Young,N; Heng,JYY; Vandeperre,LJM; Cheeseman,CR (Materials Letters, 2014)
Paper sludge ash (PSA) is a readily available waste material generated by the paper recycling industry. This work reports on the production of hydrophobic powders by dry milling PSA in the presence of a fatty acid surface functionalising agent. Optimum laboratory processing involves dry milling for 8 h with a 4 wt.% addition of stearic acid and this produced a super-hydrophobic powder with a water contact angle of 153°. Different chain length fatty acids were investigated but stearic acid produced the highest hydrophobicity. The super-hydrophobicity of PSA results from the micro-particulate texture induced by dry milling with simultaneous formation of calcium stearate self-assembling surface monolayers chemically bonded to fracture surfaces.